Role of nanoparticle materials as water-based lubricant additives for ceramics. (February 2020) - Cui, Yuxiao; Ding, Mei; Sui, Tianyi; Zheng, Wei; Qiao, Guochao; Yan, Shuai; Liu, Xibei
Abstract: The long running-in time and high wear of water-lubricated ceramics restrict their utility in the tribological field. Aqueous lubricant additives have been added to improve the tribological performance, but the effect of additive materials on the lubrication behavior is still unclear. In this study, nanoparticles of different materials were synthesized and tested for their tribological properties. The wear surfaces were systematically analyzed. The compatibility between the ceramic surface and the nanoparticles is indicated to be one of the key factors for good lubrication behavior. SiO2 nanoparticles performed cooperatively with the ceramic surface and significantly reduced the friction and wear, while ZnO and TiO2 could not form a homogenous protective film, leading to poor tribological performance. Highlights: The compatibility between the ceramic surface and the additives is one of the key factors for good lubrication behavior. SiO2  nanoparticles performed cooperatively with the ceramic surface and form homogenous protection film. With SiO2  nanoparticles, COF and WSD of water lubricated ceramics reduced for more than 70% and 50% respectively.